Large‐Scale Synthesis of Interconnected Si/SiOx Nanowire Anodes for Rechargeable Lithium‐Ion Batteries. Issue 7 (13th June 2013) - Yoo, Seungmin; Lee, Jung‐In; Shin, Myoungsoo; Park, Soojin
<x xml:space="preserve">Abstract</x> Down to the wire: Three‐dimensional interconnected Si‐based nanowires are produced through the combination of thermal decomposition of SiO and a metal‐catalyzed nanowire growth process. This low‐cost and scalable approach provides a promising candidate for high‐capacity anodes in lithium‐ion batteries.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>